2008
DOI: 10.1007/s00464-008-9943-7
|View full text |Cite
|
Sign up to set email alerts
|

Is inflammation a significant predictor of bile duct injury during laparoscopic cholecystectomy?

Abstract: We revealed that inflammation is an independent predictor of BDI occurrence during LC. Therefore, it would be advisable for surgeons to not hesitate to convert a LC to an OC in the presence of inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
1
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 26 publications
1
34
1
3
Order By: Relevance
“…Bile duct injury has been classified into 4 types. Another classification is low and high grade, depending when the leaks were identified during contrast injecton (14). Bile leaks rate is 0.3-1.35 %.…”
Section: Discussionmentioning
confidence: 99%
“…Bile duct injury has been classified into 4 types. Another classification is low and high grade, depending when the leaks were identified during contrast injecton (14). Bile leaks rate is 0.3-1.35 %.…”
Section: Discussionmentioning
confidence: 99%
“…It is now widely accepted that the inflammatory status of the gallbladder or the presence of stone migration are risk factors for complications (1). Georgiades et al (25) suggested an independent relationship between inflammation and bile duct injury. Cheema et al (26) reported a higher incidence of bile duct injury among patients who underwent delayed LC because of fibrosis and adhesions.…”
Section: Mostmentioning
confidence: 99%
“…1,2 Though a recent publication describes a decreasing rate of CBDI associated with laparoscopic cholecystectomy, 3 CBDI remains a serious concern for patients and surgeons. Despite studies identifying patient 1,4,5 and surgeon-related [5][6][7] factors associated with CBDI including inflammation and conversion to open cholecystectomy, approximately 30% of CBDI are not identified during the index operation 8 and may not be recognized until several days after the initial injury.…”
Section: Introductionmentioning
confidence: 99%